Tree fruit trade : an agricultural economist reviews fifty years of Washington state's key orchard crops - O'Rourke, A. Desmond (Andrew Desmond), 1938- (Washington State University Press, 2022)
"Filled with personal anecdotes as well as expert observation, investigation, and analysis, longtime agricultural economist Desmond O'Rourke recounts fifty years of Washington State's dynamic, internationally competitive tree fruit industry. He discusses major changes, players, and organizations, as well as significant challenges and emerging threats"--